THE RELEVANCE OF PROPHETIC SOCIAL CONCEPT ACCORDING TO KUNTOWIJOYO IN ISLAMIC EDUCATION TO PREVENT BULLYING - Abdul Aziz; Suratno Suratno (Edusoshum : Journal of Islamic Education and Social Humanities, 2023)
Bullying is an act that violates the norms of both religion and humanity. Therefore, bullying needs to be prevented while still in school. The need for prophetic social science in Islamic religious education so that students are able to control themselves to avoid bullying. This study aims to determine the relevance of Kuntowijoyo's prophetic social concept in Islamic religious education in preventing bullying. The method used is a qualitative method using library research. Data analysis in the study used Miles and Hubberman analysis in which data analysis went through three stages, namely the data reduction stage, data display and then conclusion drawing. The result is that the prophetic social idea put forward by Kuntowijoyo has three ideas, namely Humanism, Liberation, and Transcendence. This scheme is illustrated in the prophetic social concept as follows: Humanism: the creation of a conducive environment without having to differentiate from race, gender, ethnicity, and religion. Liberation: Education can foster self-confidence in their abilities and always think when doing something in accordance with religious norms. And Transcendence: Education makes the transcendental dimension the spirit in all processes in Islamic education so that students do things based on religion and piety to Allah. So that the prophetic social concept by Kuntowijoyo.